Effect of SO2 on NH3 oxidation over a Cu-SAPO-34 SCR catalyst. Issue 8 (5th February 2016) - Jangjou, Yasser; Ali, Mustafa; Chang, Qingyun; Wang, Di; Li, Junhui; Kumar, Ashok; Epling, William S.
Abstract : The impact of SO2 on NH3 oxidation, an undesired side reaction that can occur during NH3 -SCR, was studied using Cu-SAPO-34. Abstract : The impact of SO2 on NH3 oxidation, an undesired side reaction that can occur during NH3 -SCR, was studied using Cu-SAPO-34. Based on kinetic analysis, monomeric Cu ++ was active toward NH3 oxidation. In terms of the SO2 effect, significant loss in NH3 oxidation activity was observed at temperatures below 350 °C. However, at higher temperatures, SO2 had no significant effect on NH3 oxidation, which corresponds to the lack of an observed effect on SCR performance. Temperature-programmed-desorption (TPD) data obtained after NH3 and SO2 exposures demonstrate that SO2 inhibited monomeric copper NH3 oxidation activity through formation of ammonium sulfate, whose formation was catalyzed by the Cu. The monomeric copper regained NH3 oxidation activity after ammonium sulfate decomposed.